2015
DOI: 10.1371/currents.outbreaks.4211b8d6cedd8c870db723455409c0f8
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Reassortant Pandemic 2009 H1N1 Influenza Virus Outbreak in an Intensive Swine Breeding Farm: Effect of Vaccination and Enhanced Farm Management Practices

Abstract: Influenza A viruses in swine cause considerable economic losses and raise concerns about their zoonotic potential. The current paucity of thorough empirical assessments of influenza A virus infection levels in swine herds under different control interventions hinders our understanding of their effectiveness. Between 2012 and 2013, recurrent outbreaks of respiratory disease caused by a reassortant pandemic 2009 H1N1 (H1N1pdm) virus were registered in a swine breeding farm in North-East Italy, providing the oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…Our study supports previous experimental work that demonstrated high MDA measured by strain-specific HI titers reduced significantly the transmission of IAV in weaned pigs [40]. It also supports case reports where IAV elimination was attempted using IAV strain-specific sow vaccination strategies that were successful in decreasing the detection of IAV in piglets at weaning for certain periods of time [34, 35]. Notably, our results help clarify the understanding of the effect of high levels of strain-specific MDA over IAV infection in the nursery phase under field conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Our study supports previous experimental work that demonstrated high MDA measured by strain-specific HI titers reduced significantly the transmission of IAV in weaned pigs [40]. It also supports case reports where IAV elimination was attempted using IAV strain-specific sow vaccination strategies that were successful in decreasing the detection of IAV in piglets at weaning for certain periods of time [34, 35]. Notably, our results help clarify the understanding of the effect of high levels of strain-specific MDA over IAV infection in the nursery phase under field conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, other factors such as new viral introductions through gilts and people, internal biosecurity procedures including pig and people movements between farrowing rooms, and duration of herd immunity and/or sow immunity at the time of vaccination may have affected our results. Nonetheless, the fact that our findings were repeatable across farms located in several states and companies in the United States and in other studies (Chamba Pardo et al, 2018Corzo et al, 2012;Mughini-Gras et al, 2015;Reynolds et al, 2014;White et al, 2017) suggests that sow vaccination can be an effective tool for reducing IAV infections in pigs at weaning.…”
Section: Discussionsupporting
confidence: 76%
“…tiveness of sow vaccination in the control of influenza under field conditions (ChambaPardo et al, 2019;Corzo, Gramer, Kuhn, Mohr, & Morrison, 2012;Mughini-Gras et al, 2015;Ryt-Hansen, Pedersen, et al, 2019). In this study, we evaluated the effect of sow vaccination strategies on IAV infections in piglets at weaning and found that sow vaccination against IAV was effective at reducing the number of infected groups of pigs at weaning, and the number of positive pools within a group.…”
mentioning
confidence: 97%
“…Vaccination has often been used to minimize the spreading of IAV in pigs [ 11 , 12 ]. However, it is still not clear whether vaccination is an effective strategy to reduce the virus in an entire swine herd [ 12 , 13 ]. Additional studies have shown that maternally derived immunity can not only reduce clinical symptoms but also can be beneficial to reduce the spread of IAV in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…However, maternally derived immunity is effective only for a limited period of time [ 5 , 14 ]. In spite of this research into IAV transmission, it is still not well understood how the dynamics of transmission operates at the level of pig population [ 13 ].…”
Section: Introductionmentioning
confidence: 99%